2014
DOI: 10.4102/hsag.v19i1.771
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of menopause and aging in rural villages of Limpopo Province, South Africa

Abstract: Background: The term ‘menopause’ is derived from the Greek words men (month) and pausis (a cessation, a pause). It is a direct description of the psychological and physical events in women where menstruation ceases to occur. It is the time in a woman’s life when she has experienced her last menstrual bleed. Menopause is not a disease per se but a condition associated with hormonal changes where oestrogen diminishes to a low level, causing aging-related health problems. Objectives: The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…9 Ramakuela et al who conducted study among South African rural menopausal women found negative perceptions regarding menopause due to cultural factors in the villages and most of them did not have family support. 10 Ama et al assessed the perceptions among Botswana menopausal women found that majority were free from menstruation, cost of buying napkins and more relaxed while others felt as heralding medical problems such as bones becoming weak, loss of libido, vaginal discharge and prolapse. 11 In our study only 35% of them sought health care and was mainly for cardiovascular and skeletal disorders which are long term health problems.…”
Section: Discussionmentioning
confidence: 99%
“…9 Ramakuela et al who conducted study among South African rural menopausal women found negative perceptions regarding menopause due to cultural factors in the villages and most of them did not have family support. 10 Ama et al assessed the perceptions among Botswana menopausal women found that majority were free from menstruation, cost of buying napkins and more relaxed while others felt as heralding medical problems such as bones becoming weak, loss of libido, vaginal discharge and prolapse. 11 In our study only 35% of them sought health care and was mainly for cardiovascular and skeletal disorders which are long term health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been found in a field-based study from Sri Lanka by Waidyasekara et al, (2009) which showed that 66% of Sri Lanka women have experienced night sweating during menopause. Consequently, Ramakuela (2015) reported that African women have experienced sleep disturbance around the time of menopause more than other experiences.…”
Section: Unbearable Discomfort In the Bodymentioning
confidence: 99%
“…This is often regarded as a significant event in a woman's life and it is accompanied by a series of biological and psychosocial changes (Bernis & Reher, 2007) and they have to adapt to a new biological state (McKinney et al, 2012;Speroff & Fritz, 2005). The mean age of menopause is around 51years and it ranges from 45-55 years in many countries (Ramakuela, 2015;Gharaibeh, Al-Obeisat & Hattab, 2010). In Sri Lanka women's life expectancy has extended upto 79 years (Ministry of Health, 2012) and the mean age of menopause is around 51 years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations